INNOWACYJNE ROZWIĄZANIA GLOTTODYDAKTYCZNE W KSZTAŁCENIU KOMPETENCJI MIĘDZYKULTUROWEJ - Karpeta-Peć, Beata (Neofilolog, 2018)
The aim of this article is to present various innovative solutions, which can be used in foreign language teaching and learning. The essence of the discussion is the attempt to systematise the suggestions in the field of glottodidactics, which enable to fulfil the paramount aim of foreign language learning and teaching, that is the development of the cross-cultural competence.